2022
DOI: 10.3390/molecules27185962
|View full text |Cite
|
Sign up to set email alerts
|

Guanidinates as Alternative Ligands for Organometallic Complexes

Abstract: For decades, ligands such as phosphanes or cyclopentadienyl ring derivatives have dominated Coordination and Organometallic Chemistry. At the same time, alternative compounds have emerged that could compete either for a more practical and accessible synthesis or for greater control of steric and electronic properties. Guanidines, nitrogen-rich compounds, appear as one such potential alternatives as ligands or proligands. In addition to occurring in a plethora of natural compounds, and thus in compounds of phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 201 publications
0
5
0
Order By: Relevance
“…Coordination chemistry of guanidines and guanidinates has been studied extensively in the past few years. However, the research group of Robson was the first one to use triaminoguanidine-based μ 3 -ligands [(a) of Chart ] in designing trinuclear Zn­(II) and Pd­(II) complexes having a carbonate-like CN 3 core . However, they observed that during the synthesis of mononuclear Pd­(II) complexes, these ligands undergo the formation of a 1,2,4-triazole ring [(b) of Chart ] by intramolecular oxidative cyclization .…”
Section: Introductionmentioning
confidence: 99%
“…Coordination chemistry of guanidines and guanidinates has been studied extensively in the past few years. However, the research group of Robson was the first one to use triaminoguanidine-based μ 3 -ligands [(a) of Chart ] in designing trinuclear Zn­(II) and Pd­(II) complexes having a carbonate-like CN 3 core . However, they observed that during the synthesis of mononuclear Pd­(II) complexes, these ligands undergo the formation of a 1,2,4-triazole ring [(b) of Chart ] by intramolecular oxidative cyclization .…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal complexes of sym N,N 0 ,N 00 -trisubstituted guanidines, [(RN(H)) 2 C = NR] (R = alkyl-and aryl-substituents; sym = symmetrical), are known for their intriguing structures, reactivity, catalytic activity and bonding feature. [1][2][3][4][5] This class of guanidines are versatile in that the R substituent can be modulated systematically, which would enable one to fine tune their reactivity towards metal precursors. Furthermore, monoand di-deprotonation of guanidines can be carried out by choosing an external base in conjunction with the metal precursors or precursors that already contain basic ancillary ligands resulting in the formation of a great variety of guanidinate(1À) and guanidinate(2À) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The early 21 st century witnessed enormous interest in the development of bidentate monoanionic nitrogen–donor amidinate ligands of the general formula [R′C­(NR) 2 ] − , as a popular replacement for the cyclopentadienyl ligand, as well as a close association with guanidinates as the ligand architecture . Among a plethora of ligands, amidinates have been designed in such a way that the steric and electronic effects can be readily modified by tailoring the C- and N-centered substituents to stabilize and tune the reactivity of various transition metals, lanthanides, and more recently, main group compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The early 21 st century witnessed enormous interest in the development of bidentate monoanionic nitrogen–donor amidinate ligands of the general formula [R′C(NR) 2 ] − , as a popular replacement for the cyclopentadienyl ligand, as well as a close association with guanidinates as the ligand architecture. 1 Among a plethora of ligands, amidinates have been designed in such a way that the steric and electronic effects can be readily modified by tailoring the C- and N-centered substituents to stabilize and tune the reactivity of various transition metals, lanthanides, and more recently, main group compounds. Following the first use with rare-earth metals in 1992 by Edelmann et al, 2 the application of amidinates rapidly expanded and fulfilled the quest for the preparation and stabilization of low-valent main group compounds 3 10 together with applications in homogeneous catalysis 11 15 and materials chemistry.…”
Section: Introductionmentioning
confidence: 99%